CO₂ emissions and economic growth: Assessing the heterogeneous effects across climate regimes in Africa - Delphin Kamanda Espoir; Benjamin Mudiangombe; Frank Bannor; Regret Sunge; Jean-Luc Mubenga Tshitaka (ZBW - Leibniz Information Centre for Economics, 2021)
Climate change has occasioned several Earth long-term events, including extreme temperatures. In recent years, Africa was reported as part of the world's regions that experienced extreme temperatures above pre-industrial levels. Despite lower contribution to Green House Gas (GHG) emissions and global warming, Africa remains among the world regions that suffer the most from climate change. However, the impact of climatic factors of temperature and emissions on economic production in Africa has not been broadly investigated, specifically among climate regimes. In this study, we attempt for the first time to understand the heterogeneous impacts of emissions and temperature on income in Africa using panel and time-series techniques on datasets spanning the years 1995-2016. At the global level in Africa, our empirical results reveal that a 1% increase in average temperature reduces income by 1.08%, whereas a 1% rise in Co2 emissions spurs income by 0.23%. The emissions effect result implies that environmental policies specifically designed to reduce Co2 emissions in Africa as a whole may significantly impact production in the long run. Also, the result suggests that a shift from optimal temperature levels to extreme patterns deter economic growth. Despite these revelations, our extended analysis based on climate regimes indicates heterogeneous effects across countries. Considering the Paris agreement on climate, this study suggests that policymakers should emphasise country-specific policies than global climatic policies for sustained Co2 emissions reduction in Africa.
Keywords: C32; C33; Q54; 330; Heterogeneous effects; Temperature; Climate change; Environmental sustainability; Panel data; time-series data